Development and validation of volumetric absorptive microsampling coupled with UHPLC–MS/MS for the analysis of gamma‐hydroxybutyric acid in human blood. (14th January 2020) - Mohamed, Susan; Riva, Roberto; Moresco, Monica; Plazzi, Giuseppe; Contin, Manuela
Abstract: A volumetric microsampling (VAMS) device (20 μl) was evaluated and validated for the analysis of γ ‐hydroxybutyric acid (GHB) in venous blood using a simple ultra‐high‐pressure liquid chromatography–tandem mass spectrometry (UHPLC–MS/MS) method. GHB was extracted from VAMS device by acetonitrile, after a re‐hydration step in a temperature‐controlled ultrasonic bath at 60°C for 10 min. Chromatographic analysis was carried out on a Kinetex C18 column using 0.1% formic acid in water and acetonitrile as binary gradient mobile phase (from 5 to 95% of acetonitrile from 1 to 2.5 min) at a flow rate of 0.3 ml/min. The VAMS method was fully validated according to current guidelines with satisfactory results in terms of linearity, selectivity, precision, absolute recovery, matrix effect and stability. The linearity was determined from 0.5 to 200 μg/ml and the lower limit of quantitation was 0.5 μg/ml. The novel VAMS–UHPLC–MS/MS method was successfully compared with plasma‐based method in a GHB‐treated patient as a proof of concept.